Effects of different rotation cropping systems on potato yield, rhizosphere microbial community and soil biochemical properties - Qin, Junhong; Bian, Chunsong; Duan, Shaoguang; Wang, Wanxing; Li, Guangcun; Jin, Liping (Frontiers in Plant Science, 2022)
Continuous potato cropping systems cause yield reduction, soilborne disease aggravation, and soil degradation, but crop rotation can alleviate these negative effects. However, there are limited studies on the relationships between microbial community and other soil biochemical properties of continuous potato cropping at both pre-planting and harvest in North China. A 4-year study was conducted to explore the effects of different rotation system on soil biochemical properties, microbial community at pre-planting and harvest, and potato yield, tuber number and black scurf incidence at harvest in 2020 and 2021, which included 4 treatments vis. potato-potato-potato-potato (PC), potato-oat-faba bean-potato (PR), oat-faba bean-potato-oat (O), and faba bean-potato-oat-faba bean (B). The results showed that soil biochemical properties and microbial community among all treatments showed no significant difference at pre-planting after a long cold winter generally. At harvest, PC reduced tuber yield and number and significantly increased black scurf incidence relative to potato rotation systems. PC also reduced soil enzyme activities, the content of soil nutrients, and fungal community diversity, and increased bacterial community diversity compared with the other treatments, insignificantly when compared with PR. Relative abundance of microorganisms related to the degradation of organic residues, soil nitrogen cycling, and disease suppression, such as the genera Devosia, Aeromicrobium, Paraphoma, and Papiliotrema, were significantly higher in O or B than in PC and PR, while microorganisms related to disease infection such as the genera Pseudomonas, Colletotrichum, Plectosphaerella, Fusarium, and Verticillium exhibited increased in PC and PR. Principal Coordinates Analysis (PCoA) showed that there were significant differences in the microbial community structure of PC and PR at harvest compared with that of O and B. Redundancy analysis (RDA) revealed that soil available potassium (AK), acid phosphatase (ACP), available phosphorus (AP), sucrase (SUC) and pH were the dominant factors that significantly affected bacterial and fungal community structure. Partial least squares structural equation model indicated rotation system had significant negative effect on fungal community. It was concluded that growing oat or faba bean after potato can increase soil beneficial microorganisms and maintain the ecosystem healthy, thus reducing the incidence of tuber black scurf and increasing potato yield.